Power to the people energy in Europe over the last five centuries - Kander, Astrid 1962-; Malanima, Paolo 1950-; Warde, Paul ca. 20./21. Jh (The Princeton Economic History of the Western World, 2013)
Power to the People examines the varied but interconnected relationships between energy consumption and economic development in Europe over the last five centuries. It describes how the traditional energy economy of medieval and early modern Europe was marked by stable or falling per capita energy consumption, and how the First Industrial Revolution in the eighteenth century--fueled by coal and steam engines--redrew the economic, social, and geopolitical map of Europe and the world. The Second Industrial Revolution continued this energy expansion and social transformation through the use of oil and electricity, but after 1970 Europe entered a new stage in which energy consumption has stabilized. This book challenges the view that the outsourcing of heavy industry overseas is the cause, arguing that a Third Industrial Revolution driven by new information and communication technologies has played a major stabilizing role